Ամերիկեան Պորտի միսիոնարներու նամակներն ու տեղեկագիրները Այնթապի եւ Մարաշի մէջ 1922-ի գաղթականութեան հետեւանքով ստեղծուած իրադրութեան, եւ միսիոնարութեան վաղուան մասին - Չոլաքեան, Յակոբ (տպ. Atlas)
A set of 3 letters (dated 3, 5 and 13 December 1922) and 5 reports written in the Board’s Aleppo Station are brought to light in this paper. The letters describe the aftermath of the Aintab self-defense (which lasted 314 days, between April 15,1920 and February 8,1921) and particularly focus on the condition of the Armenians sheltered in the main American center in Aintab. The Board Missionaries underline the intention of the Turkish authorities, who do everything to force the Armenians to leave the city and head towards Aleppo. On their way, however, these refugees were looted and their goods ransacked. The letters speak about the role the Aintab Missionary center plays in giving refuge to Armenian refugees from Marash and Kharpert and in helping with their relocation in Lebanon and Palestine. Besides, the letters discuss the missionaries’ role after the exile of the Armenians and the eagerness of the missionaries to work with the Turks in the fields of philanthropy, health and education. The 5 reports included in this paper speak about the return of the Marash Armenians to their homeland after the armistice and the occupation of the area by the French forces, as well as the attack of Turkish militants and the deportation of the Armenians. The reports highlight the role played by Near East Relief officials in supporting the Armenians in their exile to Syria and Lebanon.
Keywords: Նամակներ; Պատմութիւն; Միսիոնարներ